Risk Factors of Ethambutol Optic Neuropathy Among Patients with Tuberculosis and NTM Infection. (4th October 2017) - Matsubayashi, Sachi; Morino, Eriko; Tsujimoto, Yoshie; Nagano, Naoko; Kakuwa, Tamaki; Sakamoto, Keita; Ishii, Satoru; Suzuki, Manabu; Takasaki, Jin; Naka, Go; Iikura, Motoyasu; Izumi, Shinyu; et al.
Abstract: Background: Ethambutol optic neuropathy (EBON) is the significant side effect of taking ethambutol (EB), and the incidence of EBON has been reported to be around 1%. The risk factors of EBON have not been appeared completely. Methods: We conducted a retrospective study to identify the frequency and the risk factors of EBON, in a medical center located in Tokyo, Japan. Patients diagnosed with tuberculosis (TB) or non-tuberculous mycobacteria (NTM) infection, who received EB, and took examination by ophthalmologists during the study period (April 2013 to March 2016), were included. Ophthalmological evaluation was done around the introduction of EB, and after emerging of any visual problems. We did the chart review, and analyzed the data between patients with and without EBON. Results: Of the 328 patients, 272 (82.9%) were with TB, and others were with NTM infection (8 are combined). The mean age was 56 years, the median duration of EB administration was 65 days, and the median dosage of EB was 13.7 mg/kg. Ten patients (3.0%) developed EBON during the study period. Rate of the elderly (≥75 years) (50.0% vs. 21.7%; 95% CI, 1.02 to 12.96; P = 0.034), and renal dysfunction (Ccr < 50) (60.0% vs. 18.4%; 95% CI, 1.82 to 24.31; P = 0.005) was significantly high in EBON patients compared with non-EBON patients. There were no significant differences in the rate of patients with diabetes, hypertension, and hyperlipidemia. Conclusion: In our study, incidence ratio of developing EBON was higher than previous reports. Age and renal dysfunction was associated with developing of EBON. Disclosures: All authors: No reported disclosures.